Potassium‐Ion Batteries: Disordered, Large Interlayer Spacing, and Oxygen‐Rich Carbon Nanosheets for Potassium Ion Hybrid Capacitor (Adv. Energy Mater. 19/2019). Issue 19 (16th May 2019) - Chen, Jiangtao; Yang, Bingjun; Hou, Hongjun; Li, Hongxia; Liu, Li; Zhang, Li; Yan, Xingbin
Abstract : In article1803894, Xingbin Yan and co‐workers report an advanced potassium ion hybrid capacitor that is constructed using carbon nanosheets as the anode and activated carbon as cathode. The device has a wide range of applications, and can meet the needs of high power density and high energy density at the same time.